Stakeholder Perspective on Challenges in Women's Football - Salmijärvi, Outi (2025)
Women’s football continues to face significant challenges rooted in historical inequalities and societal stereotypes, which have resulted in unequal resource allocation, limited media visibility, and systemic undervaluation of the women’s sport. Despite growing participation and increased attention, deeply embedded cultural and structural barriers persist, hindering the progress of gender equality in football. Therefore, this study explores gendered inequalities in women’s football, with a particular focus on how societal attitudes and institutional practices shape the sport’s development. The research examines the role of stakeholders—such as clubs, federations, sponsors, and media outlets—in promoting or hindering gender equality. Grounded in the theoretical framework of gender dynamics and stakeholder theory, the aim of this study is to emphasize the persistent gap between stakeholders’ public commitments to equality and their actual practices. The research data consists of seven semi-structured thematic interviews conducted with various stakeholders of the Finnish Kansallinen Liiga, including players, officials, and spectators. The data was analyzed using theory-guided content analysis, which helped identify how stakeholders' actions align with their stated values and map out measures for the development of women’s football. The findings reveal substantial discrepancies, particularly in resource allocation, media representation, and infrastructure support. These disparities are compounded by cultural stereotypes and systemic biases, which continue to marginalize women’s sports despite growing visibility and participation. The study concludes that stakeholders play a pivotal role in addressing these inequalities through concrete actions such as increasing investment, improving media coverage, and enhancing sponsorships. Bridging the gap between rhetoric and reality requires collaborative efforts, a shift in societal attitudes, and long-term commitments to dismantle entrenched structures that perpetuate discrimination. Ultimately, stakeholders must transition from symbolic gestures to genuine, proactive measures to create a more equitable future for women’s football.